The Influence of Celebrity Endorsements and Social Media Marketing on the Formation of Brand Equity for Yamaha Motorcycles in West Java in the City of Bandung - Arief Budiman , Adityo; Komaladewi, Rita (Coopetition : Jurnal Ilmiah Manajemen, 2024)
This study is to examine the impact of Celebrity Endorsement and Social Media Marketing on the establishment of Brand Equity for Yamaha Motorbikes in the city of Bandung, located in West Java. The use of celebrity endorsers in marketing is very prevalent, particularly due to their potential to enhance brand image. Currently, social media is progressively supplanting traditional media, and an increasing number of consumers are utilizing it as a means of obtaining information regarding products, services, and brands. Consequently, more and more brands are integrating social media marketing into their overall brand marketing strategies to take advantage of the digital revolution. The research methodology used is an explanatory approach. The study approach was conducted to acquire a methodical, objective, and precise depiction of the facts, attributes, and associations among the variables under investigation. The Structural Equation Model-SEM PLS approach was used for research data analysis. The demographic for this study consists of 220 prospective users of Yamaha Motorbikes in West Java. The study findings indicate that both celebrity endorsement and social media marketing have a substantial impact on the development of brand equity. Specifically, both celebrity endorsement and social media marketing contribute to the enhancement of brand equity.